2008
DOI: 10.1038/jp.2008.65
|View full text |Cite
|
Sign up to set email alerts
|

Association of BPD and IVH with early neutrophil and white counts in VLBW neonates with gestational age <32 weeks

Abstract: Objective: To investigate associations between early low neutrophil count from routine blood samples, white blood count (WBC), pregnancy complications and neonatal outcomes for very low birth weight infants (VLBW p1500 g) with gestational age <32 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
5
2
1
Order By: Relevance
“…Palta, M et. al found low neutrophil count (< 1*10 9 /l) predicted the BPD severity level (OR: 1.7, 95% CI:1.1–2.7) in very low birth weight (VLBW) infants [16], which is opposite to findings in the current study. Noticeably, a neutrophil count of less than 1*10 9 /l was only detected in 5 infants without BPD and 6 infants with moderate-severe BPD.…”
Section: Discussioncontrasting
confidence: 99%
“…Palta, M et. al found low neutrophil count (< 1*10 9 /l) predicted the BPD severity level (OR: 1.7, 95% CI:1.1–2.7) in very low birth weight (VLBW) infants [16], which is opposite to findings in the current study. Noticeably, a neutrophil count of less than 1*10 9 /l was only detected in 5 infants without BPD and 6 infants with moderate-severe BPD.…”
Section: Discussioncontrasting
confidence: 99%
“…A recently published study showed a strong association of early low leukocyte and neutrophil counts in preterm infants at the gestational age of <32 weeks with the severity of BPD. 21 Our data did not show higher BPD rate in the SGA group, despite lower leukocyte and neutrophil counts, compared with the AGA infants. Other investigators have reported an association between early onset neutropenia and sepsis.…”
Section: Discussioncontrasting
confidence: 73%
“…Preterm participants were recruited from the Newborn Lung Project (Palta and Sadek‐Badawi ; Palta et al. ), a cohort established at the University of Wisconsin (Madison, WI) that enrolled individuals born preterm (≤36 weeks gestation) with very low birth weight (<1500 g) in 2003 and 2004 in Wisconsin. The Newborn Lung Project also included normal birth weight (NBW) term‐born children whose addresses were obtained from 2003 to 2004 Wisconsin birth records (Palta and Sadek‐Badawi ), from which 14 controls were recruited.…”
Section: Methodsmentioning
confidence: 99%